(3GdcTGa Yf MbGFb GdJfRjds - (3eMehO Hf YeQ Hf eMeO Hf CMeO GdNhGQRej GdReNTQqj, LGQ Gddg, CHh GdbGSe,(B538 (3g`s
(3ChdgG (B:s
(3JaSjQ ShQI GdSLOI s
(3BNQgG (B:s
(3jfJgi HBNQ JaSjQ ShQI eMeO Ydjg GdUdGI hGdSdGe s
(3GdLRA GdQGHY ef GdfSNI GdeUhQI ef ecJHI GdLGeY GdcHjQ GdZQHjI HQbe (B8 (3JaSjQs
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B178 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B186 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B402s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdbGVi CMeO Hf eMeO RHGQI GdNGUI HUfYGA (B((3JaSjQ (B35) s
Keywords: (3GdJaSjQ hYdhe GdbQBfs